ANALISIS PERFORMANSI SISTEM TRANSMISI DATA PADA KOMUNIKASI FREE SPACE OPTIC TERHADAP PEGARUH VARIASI JARAK - Adistya Fajar Qolby; Sholeh Hadi Pramono; Sapriesty Nainy Sari (Jurnal Mahasiswa TEUB, 2019)
Free Space Optic (FSO) is a communication system that uses a light source in the form of an LED or LASER (light amplification by stimulated emission of radiation) and passes it to the receiver using atmospheric propagation media. In this study experimental research was conducted, namely testing and analyzing the effect of distance variations on the performance of data transmission systems in free space optical communication. For variations the distance starts from 5 cm between the location of the laser on the transmitter to the location of the photodioda on the receiver while the maximum distance is set at 50 cm. Input data used experiment experiment data transmission process in the form of word data, images, animation, and audio. Data transmission system performance is reviewed in Loss, BER, and delaytime parameters. Loss value is proportional to increasing distance variation. The greater the distance the greater the loss value. Optical loss values ​​for all types of data have started to rise when the distance is 10 cm with a 5.88 dB and receiver loss transmitter 1.1491 dB and then reach a maximum of 50 cm when the optical loss at the transmitter is 6.305 dB and the receiver is 1.3219 dB. BER values ​​obtained in each type of data tend to be constant with varying distance variations. For input data type